PTH-142 Safer steps: barriers to implementing safety interventions in a multi-site endoscopy service. (8th June 2018) - Scott, Margaret; Thomson, Richard; Donnelly, Leigh; Lee, Tom
Abstract : Introduction: World Health Organisation (WHO) checklisting is a recommended step prior to every endoscopic procedure with the potential to positively impact on patient morbidity and mortality if used effectively. Research in other settings demonstrates reduced error and improved safety where checklists are widely used, however there is evidence to suggest that significant investment is required in terms of multi-professional team-based training in order to improve safety behaviour. This study aimed to identify barriers to implementation of check listing as part of a Safer Steps programme in a large multi-site endoscopy suite. Methods: The study setting was a large endoscopy service based in the North of England. The service incorporates 32 endoscopists and 80 nurses working across 5 sites over a large geographical area. A round table exercise was conducted at a service away day. 70 nurses, administrative staff, endoscopists and managers contributed. Participants were asked to identify 'challengers' and 'enablers' to use of and pre-endoscopy checklist as part of safer steps programme including pre-list huddle, preprocedure time out, post-procedure sign-off and post-list debrief. Discussions were documented and subjected to thematic analysis. Results: Frequently encountered themes included: Conclusions: Endoscopy staff report that human factors present barriers to the performance of checklisting. There is a need to further explore the relationship between direct observation of practice and non-technical skills and whether training in human factors for endoscopy teams can reduce adverse events and improve safety behaviour.